Isothermal Adsorption of Used Cooking Oil Purification Using Avocado Seed Adsorbent - Harianingsih Harianingsih; Wara Dyah Pita Rengga; Athiya Rihadatul 'Aisy Qothrun Nada; Rizki Ria Ramadhani; Alifyan Syauqi; Retno Wulandari (Jurnal Bahan Alam Terbarukan, 2023)
High consumption of cooking oil has an impact on the availability of used cooking oil. Used cooking oil can cause pollution if the processing is not sound. So we need an alternative as a solution for handling cooking oil waste. Adsorption using avocado seed adsorbent is the choice because the morphological structure and other characteristics meet the specifications for the adsorption of used cooking oil. This study aimed to determine the acid number, viscosity, density and isothermal adsorption from avocado seeds as an adsorbent in used cooking oil. The method used was by varying the adsorbent doses of 100, 200 and 300 mg    L-1 with contact times of 30, 60, 90, 120 and 150 minutes. Adsorption was carried out at a temperature of 70oC and a stirring speed of 200 rpm. The results obtained for the acid numbers at various adsorbent doses at 150 minutes reached 6.22, 4.98 and 3.12 mg KOH      g-1. Viscosity at different adsorbents reached 54.2, 46.23 and 45.44 mm2 s-1, while the density reached 898.92, 897.17 and 896.55 kg m-3. Langmuir isothermal adsorption obtained R2 value in the equation reached 0.9365 and Freundlich reached 0.9496, so the Freundlich equation model is more recommended for use in the adsorption process because the regression value is close to 1.